Ca2+ efflux and Ca2+ signals - Green, Anne (Henry Stewart Talks, 2007)
Introduction to [Calcium]c oscillations, Involvement of Calcium fluxes in [Calcium]c oscillations, Plasma membrane Calcium efflux, Impact of Calcium efflux inhibition on [Calcium]c oscillations, Mini-glucagon as a physiological Calcium efflux inhibitor, Atrial natriuretic peptide as a physiological Calcium efflux stimulator, A hypothetical mechanism for plasma membrane Calcium flux as a determinant of [Calcium]c oscillation frequency, 'Calcium efflux modulators': a class of physiological agonists?
Archived at 2021/02/25